Phrasal Verbs in English as a Second/Foreign Language (Texas Journal of Philology, Culture and History, 2023)
Phrasal verbs are used very regularly in the English language, and native English speakers are found to use phrasal verbs on a daily basis and cannot do without the use of phrasal verbs in everyday communicative situations. However, phrasal verbs in English language teaching as a second/foreign language is almost nonexistent. That is, English as a second language (ESL)/English as a foreign language (EFL) teaching environment, in the Arab world, and specifically in Iraq, hardly teach the meaning of phrasal verbs to students, and neglect teaching the correct ways of using them, despite the fact that they are an essential part of daily native English communication. Therefore, and due to the vitality of phrasal verbs to native speakers of English, ESL/EFL students should be taught and educated to be capable of understanding and using phrasal verbs when interacting in English because knowledge of phrasal verbs would normally lead to better English language proficiency and more native-like communication. Nonetheless, phrasal verbs are not easy, and students often find them difficult, because phrasal verbs carry a specific meaning which is not inferable from the meaning of its composing words inseparable form as well as other reasons which have been explained within this paper. Hence, this paper points to the necessity of including phrasal verbs in English language teaching. Through implementing a qualitative approach, the aim, within this paper, is to identify and list causes of difficulty that learners of the English language may face when it comes to knowledge of English phrasal verbs, with regard to the spontaneous and fluent use of phrasal verbs by native English speakers. The significance, here, is to point out the need of taking this matter into serious concern and to offer suggestions and recommendations for better English as a second/foreign language learning and teaching, all in hope of better English language proficiency and ability.